Pelatihan Problem Solving Pada HMJ Teknik Informatika UIN Alauddin Makassar Menggunakan Metode Computational Thinking : Problem Solving Training at Informatics Engineering HMJ UIN Alauddin Makassar Using the Computational Thinking Method - Muhammad Syafaat (Yayasan Habiburrahman Jamalu Bina Ummat, 2022)
Student organizations are a forum for the self-actualization of students at the tertiary level, both in internal and external campus student organizations. In its journey, student organizations often encounter a number of problems, in this particular case the Student Association of the Informatics Engineering Department of UIN Alauddin Makassar which is a place for self-development for students who also often face problems in the organization. So that a special method is needed in problem-solving at HMJ TI UINAM which has a correlation with the identity of the informatics engineering department, namely the computational thinking method. Therefore, community service activities are carried out which are packaged in the form of Upgrading the management of HMJ TI UINAM to try to apply this method to student organizations where it is hoped that the management of HMJ TI UINAM will gain new knowledge in dealing with problems in the organization. After this service was carried out, it was found that the administrators were very enthusiastic in doing role play in the training so that they already knew that computational thinking methods could be applied well in solving problems in organizations.